EVALUASI DAN SELEKSI 24 GENOTIPE JAGUNG LOKAL DAN INTRODUKSI YANG DITANAM SEBAGAI JAGUNG SEMI - Surjono Hadi Sutjahjo; Hadiatmi Hadiatmi; Meynilivia Meynilivia (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
The objectives of this research were to characterize 24 corn genotypes and to select the best genotype to be grown as baby corn having high yield and early harvesting. The results indicated high genetic variability for all characters meaning that there was a great chance for further selection on characters of interest. Genotypes which have the highest number of cob were Lokal Rempek and Pena Boto. Pena Boto also has the lowest damage cobs. Lokal Dea and Lokal Nala were the earliest harvesting genotypes. Genotype Arjuna, Lokal Tumbu and Lokal Nala showed the highest baby corn yield. Considering all characters observed, Arjuna, Pena Boto, DT-6, Lokal Lendang Ree, Lokal Rempek, and Lokal Tumbu were the best baby corn genotypes in this study.